Flash of light, wall of fire Japanese photographs documenting the atomic bombings of Hiroshima and Nagasaki - Stoff, Michael B. (University of Texas Press, 2020)
"In 1945, American forces authorized the release of photographs taken by Japanese citizens in the immediate aftermath of the bombings of Hiroshima and Nagasaki. Many of these images survived as a result and became part of the Hiroshima and Nagasaki Atomic Bomb Photographs Archive, now housed at the Briscoe Center for American History. The archive consists of more than eight hundred photographs, over one hundred of which are collected here. Accompanying a major exhibition at the Briscoe Center in 2020 to be held on the seventy-fifth anniversary of the bombings, Flash of Light, Wall of Fire features the work of twenty-three Japanese photographers who risked their lives to capture the devastation. These harrowing images serve as visual documentation of nuclear blast damage and destruction, the burnt human flesh, the horrific after effects of radiation, and the mass human suffering that ensued. An introductory essay from Michael B. Stoff and an afterword by Japanese journalist Michiko Tanaka--who grew up in post-war Hiroshima--explore how the images were obtained and how they helped provoke calls for peace and the abolishment of nuclear weapons."--
Keywords: Briscoe Center for American History; Geschichte 1945; Sammlung; Dokumentarfotografie; Atombombenabwurf -- Motiv; Hiroshima; Japan; Nagasaki; Hiroshima-shi (Japan) / History / Bombardment, 1945 / Pictorial works; Nagasaki-shi (Japan) / History / Bombardment, 1945 / Pictorial works; Atomic bomb victims / Japan / Hiroshima-shi / Pictorial works; Atomic bomb victims / Japan / Nagasaki-shi / Pictorial works; Hiroshima and Nagasaki Atomic Bomb Photographs Archive (Dolph Briscoe Center for American History) / Photograph collections / Exhibitions; Dolph Briscoe Center for American History / Exhibitions; Atomic bomb victims; Photograph collections; Japan / Hiroshima-shi; Japan / Nagasaki-shi; 1945; Exhibition catalogs; History; Pictorial works; Bildband